Wealth and poverty in European rural societies from the sixteenth to the nineteenth century - Broad, John; Schuurman, Anton (2014)
This book sheds new light on old problems of wealth, poverty and material culture in rural societies. Much of the debate has concentrated on north-west Europe and the Atlantic world. This volume widens the geographic range to compare less well known areas, with case studies on the Mediterranean world (Catalonia and Greece), from central Europe (Bohemia and Hungary), and from the Nordic countries (Denmark). Methodologically, several papers link the possession of goods to the use of room space, while others highlight the importance of the channels for the circulation of goods, problems of stocks and flows of goods, and the complexities of urban/rural difference. Finally, this book seeks to stimulate new comparative studies in living standards and lifestyles by providing an overview of achievements up till now.